Influence of pH and temperature on alunite dissolution: Rates, products and insights on mechanisms from atomistic simulation - Acero, P.; Hudson-Edwards, K.; Gale, Julian (2015)
The processes, rates, controlling factors and products of alunite (KAl3(SO4)2(OH)6) dissolution were assessed using batch dissolution experiments at pHs of c. 3, 4, 4.6, 7 and 8, and temperatures of c. 280, 293 and 313K. Alunite dissolution is roughly congruent at pH3, while at pH=3.9 the process is incongruent, giving a lower Al/K ratio in solution than in the pristine alunite sample. The decrease in the Al/K ratio appears to be caused by precipitation of secondary aluminium sulfate/hydroxysulfate minerals coating the surface of the dissolving alunite, as inferred from SEM images and XPS determinations, but these minerals do not passivate the alunite surface for the time frame of the experiments (up to 400h). The lowest dissolution rates are obtained for pH4.6 and 280K. Both the temperature increase and any pH variation from that point lead to faster dissolution rates. Based on the potassium release to solution, the influence of pH and temperature on the alunite dissolution rate for pH of 4.8 and below can be expressed as;. rateK = 10 4.4 ± 0.5aH+ 0.10 ± 0.02e 32±3/RT where rateK is the alunite dissolution rate (in mol·m-2·s-1); aH+ is the activity of hydrogen ions in solution; R is the Universal gas constant (in kJ·mol-1·K-1) and T is temperature (in K).For pH of 4.6 and above, the alunite dissolution rate can instead be expressed as;. rateK = 102.5±0.8aOH 0.14±0.02e-39±4/RT where aOH- is the activity of hydroxyl ions in solution. In light of the calculated values for the activation energy under the two sets of pH conditions (32 ± 3 and 39 ± 4 kJ·mol-1), alunite dissolution appears to be surface-controlled. Examination of the most stable solvated alunite surfaces obtained by atomistic computer simulations suggests that the least energetically favourable steps during alunite dissolution are the detachment of either Al atoms or SO4 tetrahedra from exposed surfaces. Thus, these processes are most probably the rate-determining steps in alunite dissolution.